Evaluation of seedling emergence and relative DNA content under dry soil conditions of wild Festuca arundinacea populations collected in Iran. (20th January 2015) - Rohollahi, Iman; Khoshkholghsima, Nayer Azam; Yamada, Toshihiko; Kafi, Mohsen; Hoshino, Yoichiro; Liaghat, Abdolmajid; Jafari, Ali Ashraf
Abstract Tall fescue (Festuca arundinacea Schreb.) is an important forage and turf grass species adapted to cold, arid and semiarid environments. Germination and seedling establishment of F. arundinacea cultivars is constrained by the low soil moisture found in these regions. Genome size was found to positively correlate with latitude of origin, suggesting that structural changes in DNA may play a role in environmental adaptation. We investigated the effects of low soil moisture on the germination and early establishment and their correlation with relative DNA content using 14 wild F. arundinacea populations collected from various regions in Iran and two commercial turf cultivars. The populations were evaluated under 100% (−0.03 matric potential [MPa]), 80% (−0.2), 60% (−0.6) and 40% (−1.4) field capacity (FC) conditions. Seed germination and root and leaf growth decreased under reduced soil water content. Cluster analysis revealed that the populations fell into four groups. Populations in cluster I showed the greatest tolerance to low soil moisture and cluster IV was the least tolerant. 'Isfahan' and 'Gonabad' populations had the best final germination and longer leaf and root length at 40% FC. Studies to identify indices that were involved in drought resistance revealed that final germination, leaf length and seedling vigor index were most important evaluating indicators for F. arundinacea populations. Flow cytometric relative DNA content of the wild populations was negatively correlated with germination, leaf length and seedling vigor index. The drought tolerance populations in cluster I could be potentially useful germplasm for a breeding program to develop superior cultivars for arid and semiarid regions.